Empowering Bumdes: Financial Management Driving Business Growth in Pacitan - Firmansyah, Amrie; Irawan, Ferry; Arfiansyah, Zef; Qadri, Resi Ariyasa; Wijaya, Suparna (Accounthink : Journal of Accounting and Finance, 2024)
Good financial management is a key factor in supporting the development of Village-Owned Enterprises (BUMDes) as drivers of the village economy. This study aims to identify and analyze the impact of financial management on the development of BUMDes businesses in Pacitan Regency, with a focus on advanced BUMDes categories. Effective financial management is believed to be able to increase the transparency, accountability, and competitiveness of BUMDes amid market dynamics. The research method used is a qualitative approach, with in-depth interviews involving four informants, namely two BUMDes Directors, one representative of the Community and Village Empowerment Service of Pacitan Regency, and one Community Empowerment Expert. This study explores financial management practices, challenges faced, and business development strategies implemented by advanced BUMDes. The results of the study indicate that good financial management, including the application of accounting technology, plays an important role in increasing efficiency and transparency. However, there are still challenges in long-term planning and limited access to capital due to strict regulations. This study concludes that BUMDes that can implement effective financial management have a greater opportunity to develop their business. This study indicates that the Pacitan District Government needs to strengthen advanced training programs, technical assistance, and policies that support easy access to capital for advanced BUMDes so that they can continue to develop and contribute more to the village economy